Indonesia's Cyber Defense Strategy in Mitigating The Risk of Cyber Warfare Threats - Agus Permana (Syntax Idea, 2021)
The purpose of this paper is to analyze and describe the strategy of the Indonesian government in mitigating the risk of dealing the threat of cyber warfare. This paper uses the qualitative method using 3 indicators of risk mitigation theory consisting of prevention, indentification and remedy to interpret the problem and explain it in more detail by collecting data from literature studies. Cyber defense threat mitigation refers to policies and processes put in place by an institution to help in preventing a potential security incident and data breaches as well as to limit the extent of damage when a security attack does happen. The results of the discussion of this study are the Indonesian government's strategy focusing on processes, technology and information, preparedness, response, and follow-up activities, all of which included in instruments for measuring risk mitigation of cyber warfare threats. The conclusion is that Cyber defense in the form of a strategic concept must be concrete if all infrastructure networks are held, then the cyber defense policy can be known. To build a reliable cyber defense system, the government and stakeholders must ensure that the cyberinfrastructure is secure. The Indonesian government must increase capacity and increase cooperation leading stakeholders and government is essential regarding cyber warfare. Having a good risk mitigation plan will help cyber defense policies in Indonesia as the basis for the preparation.